Analysis of Decreasing Sales Turnover of Muslim Clothes in Tanah Abang Market Jakarta - Kumala, Destiana; Herawati, Ermi; Haryadi, Rofiq Noorman (Jurnal Manajemen Bisnis dan Keuangan, 2024)
Since 2012, sales volume at Tanah Abang Wholesale Market has experienced a downward trend; worst of all, in 2018, approximately 30% lost regular customers. Sales turnover is the total number of sales of goods or services within a certain period, which is calculated based on the amount of money earned and based on volume. The leading cause of the decline in turnover in the Tanah Abang market block B is the COVID-19 pandemic. Due to restrictions on socializing activities in the community, commonly referred to as PSBB, a new government policy, all traders in the Tanah Abang market block B are also affected. Traders improve and develop management and sales strategies to compete with the modern market.